How online courts effectively supplement digital trade and contribute to sustainable development goals: Insights from a case study of China - Martin Yat-cheung Kwan (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2024)
The increasing volume of digital trades inevitably generates more disputes. An efficient online dispute resolution mechanism is an important digital trade promotion policy measure, as it ensures the cyber order and strengthens online users' confidence. The immediate implication is the furtherance of Sustainable Development Goal (SDG) 16.3 on better access to justice and SDG 16.7 on having a responsive judiciary. But having an online judiciary does not only improve SDG 16. Drawing insights from the Internet Courts in China, the disputes arisen from the voluminous amount of digital trades provide more opportunities for the judiciary to contribute to other SDGs, such as SDG 2 (food safety), 3 (public health), 4 (online education), 8 (equality), 9 (intellectual property and innovation) and 10 (employment). Whilst digital trades can promote SDGs, they are usually private/commercial interests-oriented and only incidentally benefit the SDGs. Inevitably there will be occasional problems (e.g. irresponsible commercial behavior or market failures) which could undermine the SDGs. By contrast, the online courts are public interests-oriented, with the goal of maintaining public order and development. This legal policy measure helps align private digital trades and public SDGs. The judgements-coupled with widespread news reporting and subsequent response by other relevant public organs-help monitor and ensure proper sustainable development.
hdl:20.500.12870/6769
Keywords: K33; K41; L86; Q01; 330; Digital trade; E-commerce; Online dispute resolution; E-commerce dispute resolution; E-commerce law; China Internet Courts; SDGs